Democracy or Dictatorship? : Which political system helps economy to grow faster? - Zhadger, Assem; Špecián, Petr; Slaný, Martin, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2020)
The thesis concerns the question of the importance of the political system in economic development. My research investigates whether dictatorship or democracy generate higher economic growth. The growth rate is measured by GDP per capita. The discussion starts with a short literature review regarding the political regime and economic prosperity. Afterwards, I summarize earlier statistical evidence and create my own OLS models. The model includes GDP per capita growth as the main independent variable and trade level, population growth, investment rates, and corruption level as dependent variables. The time range is between 2000 and 2019. I select all the states based on their democracy index and data from the world bank. The conclusion is that the dictatorship countries are more successful in term of GDP per capita growth. The corruption level negatively affects the GDP per capita growth under the dictatorship, and the corruption level is lower in democracies. The trade positively influences on dictatorial countries, but negatively effects on states under democracies. In both regimes, the investment level is statistically significant. But in democracies, investment leads to higher growth in comparison with dictatorships. The population growth is insignificant in both political systems. The last thing is years in power negatively impact on GDP per capita growth.
Vedoucí práce: Petr Špecián
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses